Protective Value of Aspirin Loading Dose on Left Ventricular Remodeling After ST-Elevation Myocardial Infarction - Calvieri, Camilla; Galea, Nicola; Cilia, Francesco; Pambianchi, Giacomo; Mancuso, Giuseppe; Filomena, Domenico; Cimino, Sara; Carbone, Iacopo; Francone, Marco; Agati, Luciano; Catalano, Carlo (Frontiers in Cardiovascular Medicine, 2022)
Aims: Left ventricular (LV) remodeling after ST-elevation myocardial infarction (STEMI) is a complex process, defined as changes of LV volumes over time. CMR feature tracking analysis (CMR-FT) offers an accurate quantitative assessment of LV wall deformation and myocardial contractile function. Our aims were to evaluate the role of myocardial strain parameters in predicting LV remodeling and to investigate the effect of Aspirin (ASA) dose before primary coronary angioplasty (pPCI) on myocardial injury and early LV remodeling. Methods and results: In this cohort retrospective study, seventy-eight patients undergoing to CMR, within 9 days from symptoms onset and after 6 months, were enrolled. We divided the study population into three groups based on a revised Bullock’s classification and we evaluated the role of baseline CMR features in predicting early LV remodeling. Regarding CMR strain analysis, worse global circumferential and longitudinal strain (GCS and GLS) values were associated to adverse LV remodeling. Patients were also divided based on pre-pPCI ASA dosage. Significant differences were detected in patients receiving ASA 500 mg dose before pPCI, which showed lower infarct size extent and better strain values, if compared to those treated with ASA 250 mg. At stepwise multivariate logistic regression analysis, adjusted for covariates, a 500 mg ASA dose remained an inverse independent predictor of early adverse LV remodeling. Conclusion: GCS and GLS have high specificity to detect early LV adverse remodeling. We firstly reported a protective effect of ASA loading dose of 500 mg before pPCI on LV myocardial damage and in reducing early LV adverse remodeling.